2007
DOI: 10.1111/j.1538-7836.2007.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative kinetics of clotting and lysis provide a biochemical rationale for the correlation between elevated fibrinogen and cardiovascular disease

Abstract: To cite this article: Kim PY, Stewart RJ, Lipson SM, Nesheim ME. The relative kinetics of clotting and lysis provide a biochemical rationale for the correlation between elevated fibrinogen and cardiovascular disease. J Thromb Haemost 2007; 5: 1250-6. Summary. Background: Elevated plasma fibrinogen is a well known risk factor for cardiovascular disease. The mechanistic rationale for this is not known. Objectives: These studies were carried out to determine the fibrinogen concentration dependencies of clotting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 29 publications
1
45
0
1
Order By: Relevance
“…Fibrin 100 was also found to be more resistant to fibrinolysis in the "bubble release" assay format, where measurements do not depend on clot turbidity changes and tPA is incorporated throughout the clot (data not shown). In this format, there was also a small but consistent decrease in tPA potency in fibrin 100 such that tPA had 86.9% (83.1%-90.8%) potency compared with fibrin 10 .…”
Section: Enzyme Kinetic Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Fibrin 100 was also found to be more resistant to fibrinolysis in the "bubble release" assay format, where measurements do not depend on clot turbidity changes and tPA is incorporated throughout the clot (data not shown). In this format, there was also a small but consistent decrease in tPA potency in fibrin 100 such that tPA had 86.9% (83.1%-90.8%) potency compared with fibrin 10 .…”
Section: Enzyme Kinetic Studiesmentioning
confidence: 99%
“…Figure 2 shows how the potency of tPA was markedly affected by the nature of the fibrin, but the effect diminished as tPA concentration increased. In this representative example, the lowest tPA dose (0.15nM) had a more than 2-fold higher potency as plasminogen activator in fibrin 100 compared with fibrin 10 . By contrast, fibrinolysis rates in the same clots (turbidity changes in the clot, not shown) were slower in fibrin 100 such that tPA potency was calculated to be 73.8% (62.1%-87.1%) as active in fibrin 100 compared with fibrin 10 .…”
Section: Enzyme Kinetic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we found that well known inflammatory markers that reflect vascular inflammation such as fibrinogen, hs-CRP and NLR levels were higher in patients with intermediate-high SXscore. In addition, fibrinogen contributes to blood viscosity, platelet aggregation, and fibrin formation and modulates subsequent coagulation activation [21]. Fibrinogen has been shown to promote smooth muscle cell proliferation and induce monocyte chemotaxis [22].…”
Section: Discussionmentioning
confidence: 99%